Jacob Schiff and the Art of Risk American Financing of Japan's War with Russia (1904-1905) - Gower, Adam (Palgrave Studies in the History of Finance,, 2018)
"A fascinating, wholly new, account of the emergence of Japan as a major player in the global economy and politics in the early twentieth century, and New York financier Jacob Schiff's role in funding it, while he boosted the US challenge to the City of London's dominance in world finance." -Patricia M. Thane, MA (Oxon), PhD (LSE), FBA, Research Professor in Contemporary British History, Department of Political Economy, King's College, London "Jacob Schiff and the Art of Risk showcases the fascinating stories and insights of how international banking worked in the early 20th century and how it still works today. It uniquely illustrates how one banker shifted the paradigm and opened the door for New York to replace London as the center of international finance." -Doug Krause, General Counsel and Chief Risk Officer of East West Bank; Director of the Western Bankers Association and the International Bankers Association of California "Jacob Schiff, a prominent New York Jewish banker, assembled the loans that Japan required for its war with Russia in 1905. This book covers a fascinating tale of a great Wall Street bank in the setting of Manhattan society, the global expansion of American finance, and the rise of modern Japan." -Avner Offer, Chichele Professor Emeritus of Economic History, University of Oxford.